The inheritance of hunting traits in German hunting terriers - Werneyer, Amelie (2019)
A convenient method for efficient and successful hunting – in accordance with the animal protection laws – is the service provided by hunting dogs. Approximately 12 000 – 18 000 years ago humans domesticated dogs for hunting purposes (Braastad & Bakken, 2002; Sablin & Khlopachev, 2002; Germonpré et al. 2008). During the time of breed creation dogs were selected for certain traits like for instance hunting (e.g. tracking or flushing), guidance, and protection (Naderi et al. 2001). Still today selection and other breeding measures help to improve the performance (Holloway et al. 2011) of hunting dogs (Ruusila & Pesonen, 2004).